The Expungement of Adjudication Records of Juvenile and Adult Offenders: A Problem of Status - Aidan R. Gough (Washington University Law Quarterly, 1966)
This Article will attempt to survey the need for legislation allowing the expungement of an adjudication record of a juvenile or a conviction record of an adult first offender. It will attempt to examine existing and proposed statutes on both adult and juvenile court levels, and to make some evaluation of their effectiveness. It is the writer’s view that providing institutional means of restoring status after reformation is an appropriate way to harmonize “the sanctioning activities of the democratic body politic with the ultimate value-human dignity.”
Keywords: Documents and records; Juvenile courts